CHANGES IN THE DIASTOLIC FUNCTION OF THE HEART AND TUMOR NECROSIS FACTOR-ALPHA IN PATIENTS WITH COMBINED PATHOLOGY: ARTERIAL HYPERTENSION WITH TYPE 2 DIABETES AND OBESITY - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.M.; Starenky, V.P.; Kuzminova, N.V.; Krivoshapko, A.V.; Abramova, L.P. (World of Medicine and Biology, 2023)
The purpose of the work was to study the features of the diastolic function of the left ventricle and the tumor necrosis factor-α level in patients with combined pathology: arterial hypertension with type 2 diabetes and obesity. Disorders of the diastolic function of the left ventricle were established to be more often registered in patients with arterial hypertension with type 2 diabetes and obesity, compared to the group of patients with arterial hypertension and type 2 diabetes with normal body weight. A significant increase in the content of tumor necrosis factor-α was determined in the group of patients with arterial hypertension with type 2 diabetes and obesity compared to the group with arterial hypertension and type 2 diabetes with normal body weight.